PENGARUH FLUKTUASI TINGGI MUKA AIR TERHADAP ZAT PENCEMAR PADA DRAINASE DENGAN OUTLET DI SUNGAI SEBANGAU - Saputra, Krisna Jalu Adityas; Yupi, Haiki Mart; Kamiana, I Made (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2024)
Urban drainage channels are very easily contaminated by pollutants from household waste, industrial waste, and other liquid waste. Therefore, the main (primary) drainage channels have the potential to affect water quality in the Sebangau River. This study aims to determine the contribution of pollutants from drainage channels. The location of this study is in the Jekan Raya District, Palangka Raya City, Central Kalimantan Province, precisely in one of the primary drainage channels with a total length of drainage channels with a distance of ± 3.6 km to the Sebangau River outlet located on Jl.Tampung Penyang. To obtain the flow rate in the drainage channel, the water velocity and water level are measured in each rai to obtain the cross-sectional area of ​​the channel, then the water discharge is calculated by multiplying the velocity and cross-sectional area of ​​the channel. Water quality is analyzed in the laboratory based on several predetermined parameters such as acidity level (pH), TSS, ammonia, detergent, BOD, COD, oil and fat, and after all data is collected, Anova statistical analysis is carried out to determine the relationship between water level and each parameter. The results obtained indicate that fluctuations in water levels in the main drainage channel, in the middle, affect the parameters of detergent pollutants only, indicated by the value of R2 = 0.593 (moderate), and the correlation coefficient (r) = 0.770 indicating that the relationship between fluctuations in water levels and detergent parameters has a strong correlation. However, for several other pollutant parameters observed, namely pH correlation coefficient (r) = - 0.590 (fairly correlated), TSS correlation coefficient (r) = - 0.500 (fairly correlated), ammonia correlation coefficient (r) = - 0.889 (fairly correlated), BOD correlation coefficient (r) = 0.041 (very weakly correlated), COD correlation coefficient (r) = - 0.250 (weakly correlated), oil and fat correlation coefficient (r) = 0.400 (fairly correlated). Showing that pollutants in the form of detergents from the main drainage channel contribute to pollution of water bodies in the Sebangau River.